Young adults' relationship intentions towards their cell phone network operators - L. Kruger; P. G. Mostert (South African Journal of Business Management, 2012)
Marketers use relationship marketing to establish mutually beneficial long-term relationships with their customers as a means to retain them in the competitive market environment. Relationship marketing should not be used to target every customer as not all customers want to build long-term relationships with organisations. In order to identify the most profitable customers for relationship marketing, organisations should consider their customers' relationship intentions to form long-term relationships with them. The primary objective of this study was to determine young adults' (aged 18 to 25) relationship intentions towards the South African cell phone network operators they use, namely Vodacom, MTN or Cell C. Five constructs (involvement, expectations, forgiveness, feedback and fear of relationship loss) were used to measure relationship intention. Data was collected from 315 respondents at a tertiary education institution in South Africa by means of a non-probability convenience sample. Findings indicate that a relatively high percentage of respondents have a high relationship intention towards their cell phone network operator and that respondents with high relationship intentions are more Involved with and Fear losing their relationship with their cell phone network operator than respondents with low relationship intentions
Keywords: 650